Inflammation and the Association of Vitamin D and Depressive Symptomatology. - Dogan-Sander E; Mergl R; Willenberg A; Baber R; Wirkner K; Riedel-Heller SG; Röhr S; Schmidt FM; Schomerus G; Sander C (MDPI (Basel, Switzerland), 2021)
Depression and vitamin D deficiency are major public health problems. The existing literature indicates the complex relationship between depression and vitamin D. The purpose of this study was to examine whether this relationship is moderated or mediated by inflammation. A community sample (n = 7162) from the LIFE-Adult-Study was investigated, for whom depressive symptoms were assessed via the German version of CES-D scale and serum 25-hydroxyvitamin D (25(OH)D) levels and inflammatory markers (IL-6 and CRP levels, WBC count) were quantified. Mediation analyses were performed using Hayes’ PROCESS macro and regression analyses were conducted to test moderation effects. There was a significant negative correlation between CES-D and 25(OH)D, and positive associations between inflammatory markers and CES-D scores. Only WBC partially mediated the association between 25(OH)D levels and depressive symptoms both in a simple mediation model (ab: −0.0042) and a model including covariates (ab: −0.0011). None of the inflammatory markers showed a moderation effect on the association between 25(OH)D levels and depressive symptoms. This present work highlighted the complex relationship between vitamin D, depressive symptoms and inflammation. Future studies are needed to examine the effect of vitamin D supplementation on inflammation and depressive symptomatology for causality assessment.
Keywords: LIFE-Adult-Study; depression; inflammation; mediation; moderation; vitamin D; Adult; Aged; Biomarkers; Depression; Humans; Inflammation; Male; Middle Aged; Models, Biological; Regression Analysis; Vitamin D; Young Adult